Choice of transport in urban and periurban zones in metropolitan area. (April 2022) - Obregón-Biosca, Saúl A.
Abstract: The choice of transport is a user decision defined by transport attributes and user characteristics. In a sprawl area in an emerging economy, the determining factors can be analyzed by considering a metropolitan area, the user residence area, the conurbation, or a periurban area. To determine the main user characteristics affecting transport choice in urban and periurban zones, the transport choice was analyzed using discrete choice models considering user characteristics and transport attributes. A case study was conducted in the Queretaro metropolitan area (QMA). Four transport modes were analyzed: car and bus (motorized), and bicycle and walking (active). The peripheral and conurbed zones were compared, considering the four transport modes. The results show that user income is a determinant in motorized transport choice; age and gender are determinants in active transport choice. Highlights: User income is a significant variable in motorized transport choice in urban and periurban zones. In both zones, income and education are socioeconomic user characteristics that determine the choice of motorized transport. For active mobility in the peripheral zone, age is a determining factor in the transport choice. For active mobility in the conurbed zone, the gender is a factor; men choose a bicycle more often in the conurbation.